Analyzing Teachers' Feedback and Challenges on Students' Speaking Skills at Smp Negeri 16 Mataram - Muhammad Hulaipi Rais; Soni Ariawan; Suhandra, Ika Rama; Septiyana, Himayatinnisa (Yayasan Sinergi Kawula Muda, 2025)
Teacher feedback plays a crucial role in enhancing students' speaking skills, motivation, and confidence in learning English as a foreign language (EFL). This study aims to investigate the types of feedback provided by English teachers and the challenges they encounter in offering feedback at SMP Negeri 16 Mataram. Using a qualitative research approach, data were collected through interviews with 2 teachers and 5 students. The findings reveal that teachers primarily used positive and constructive feedback to encourage students’ participation and improvement. However, teachers face several challenges, including students' lack of interest, low motivation, and difficulties in pronunciation and grammar. This study highlights the need for effective feedback strategies and interactive teaching methods to enhance student engagement and learning outcomes.